DIGITALISASI UMKM : PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PEMASARAN KERIPIK BABY FISH di DESA GEDONG BOYOUNTUNG LAMONGAN - Sri Yaumi; Tri Winarsih; Ananda Yuniar; Yuliana Dewi Safitri; Suhari; Lusi Nur Widyawati; Hermanto Hadi; Abdul Majid (CV. ALIM'SPUBLISHING, 2023)
The Covid 19 pandemic has impacted changes in business activities. Trading activities that were previously carried out conventionally have now become completely digital. With this change, not all MSMEs have sufficient knowledge and ability to use social media. This causes MSME players who do not follow these changes to be unable to compete with other MSMEs that are already selling online. The purpose of this community service is to provide assistance in creating Facebook, Instagram and WhatsApp social media accounts and then teach them how to promote and sell online on these accounts. The method used in this activity is the practice of creating social media accounts and uploading merchandise. The result of this activity is that UMKM Baby Fish Chips are able to sell online through the social media Facebook, Instagram and whatsapp.